Revitalisasi Birokrasi Menuju Indonesia Baru - Erwan Agus Purwanto (Centre for Public Policy and Management Studies, 2005)
Bureaucracy is main executor for reform agendas. Therefore in realizing all of reform agendas in Indonesia, then bureaucratic reform is an underlying effort supposed to do. There are two prerequisite should be fulfilled for the reform. Firstly, there must be some endeavours to shift the old basic value of bureaucracy and the secondly, some endeavours directed to acativate interaction process among government, private sector and civil society in responding public affairs in their environment.Kata kunci: birokrasi, revitalisasi, pergeseran nilai, good governance, warga